Deteksi Lapisan Bawah Permukaan di Desa Wajok Hilir Menggunakan Metode Geolistrik Resistivitas Konfigurasi Wenner-Schlumberger - Aisyah Rafa; Zulfian Zulfian; Radhitya Perdhana; Joko Sampurno; Irfana Diah Faryuni (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
Research on the detection of subsurface layers using the Wenner-Schlumberger resistivity geoelectrical method was conducted in Wajok Hilir Village, Mempawah Regency, West Kalimantan Province. This research employed a Geotitis GL-MD-300 resistivity meter. The survey was conducted along three lines, each 260 m in length, using the geoelectrical method. Based on the two dimensional modeling results, the three lines exhibit resistivity values ranging from 5.69 to 3890 Ωm, and interpreted as three subsurface layers: a clay layer at depths of approximately 2,5 until 18.5 m with resistivity values of 5,69 until 237 Ωm, a sandy clay layer at depths of 2.5 until 24.9 m with resistivity values of 237 until 1531 Ωm, and a sand layer extending to depths of up to 39.6 m with resistivity values of 1531 until 3890 Ωm. This information on subsurface layers can be used as supporting data for development planning, environmental management, and hazard mitigation in the region.